Determinação da forma do objeto troiano (624) Hektor a partir de inversão de curva de luz e ocultações estelares - Spina, Fabio Augusto (2021)
The study of the Solar System’s small bodies can reveal information about the circumstances of the system’s formation. Among these objects, the Trojans are of special interest. Found at the Lagrange equilibrium points L4 and L5 along the orbits of a planet, they possibly preserve some features that date back to the formation of the Solar System (NESVORNY, 2021). This work aims to refine the knowledge about the shape of (624) Hektor, the largest Trojan of the planet Jupiter, through the light curve inversion technique (KAASALAYEN et al., 1992a,b) combined with stellar occultations. Situated at point L4, (624) Hektor was discovered in 1907 and has an estimated diameter of 233 km (MARCHIS et al., 2006; HANUS, 2015; ROZEHNAL et al., 2016). We analyzed 93 rotational light curves observed between 1957 and 2020, being the most recent obtained during this work, based on observations carried out at the Pico dos Dias Observatory. Through the analysis of these data, it was possible to obtain the rotational period of P = 6.920509 h ± 0.000001 h, which was used in the light curve inversion technique, a procedure that considers, among other properties, the scattering of the object’s surface and its rotational characteristics. This procedure was performed using the Convexinv software (ĎURECH, 2010) and the results obtained allowed us to estimate the coordinates of the rotation pole (λ = 331.80° ± 10° and = -27.00° ± 10°) and a possible convex shape represented by a 1018 polyhedron faces and 2032 vertices, but with a dimensionless volume. These results were used as a parameter for the ADAM software (VIIKINKOSKI, 2015), which combined the 93 light curves with 10 chords from a stellar occultation observed in 2019 and another 5 obtained in 2020 by the Rio Group. The combination of light curves with the occultations chords allowed to refine the shape determination, and the non-convex model generated, with 800 faces and 402 vertices, with pole λ = 334° ± 10° and = -25° ± 10°, and equivalent volumetric diameter of 193 km ± 20 km, which allowed to estimate the density of (624) Hektor as ρ = 2.11 + 0.65 g/cm³. These results are compared with those already available in the literature and, in particular, with the bilobal format suggested by Marchis et al. (2006), which is not compatible with the observed occultation chords and, therefore, is refuted by the results of this work. We hoped that this study can contribute to the research of small bodies by presenting ways to determine precise physical characteristics for these irregular objects, thus contributing to the effort to understand the primordial conditions in which these and possibly other objects formed and evolved. It is also expected that these results add to those that will be obtained by the Lucy mission (NASA), scheduled for launch in October 2021, which will study other 6 Trojans of Jupiter between 2025 and 2033.